Analisis Kelayakan Finansial dan Strategi Pengembangan Teh Gaharu di Kabupaten Bangka Tengah (Studi Kasus: Teh Gaharu âAqillaâ Gapoktan Alam Jaya Lestari) - Karsiningsih, Eni (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2016)
This study aims to analyze feasibility of agarwood tea business, to describe marketing strategies of agarwood tea, and to analyze the business development strategy of agarwood tea